Work aggravated asthma in Great Britain: a cross-sectional postal survey. Issue 6 (12th April 2018) - Bradshaw, Lisa; Sumner, Jade; Delic, Julian; Henneberger, Paul; Fishwick, David
Abstract : Objective: Work aggravated asthma (WAA), asthma made worse by but not caused by workplace exposures, can have a negative impact on personal, social, financial and societal costs. There is limited data on prevalence levels of WAA in Great Britain (GB). The objective of this study was to estimate the prevalence of WAA in GB, and to assess its potential causes. Materials and methods: A cross-sectional postal questionnaire study was carried out. A total of 1620 questionnaires were sent to three populations of adults with asthma. The questionnaire recorded; demographic details, current job, self-reported health status, presence of asthma and respiratory symptoms, duration and severity of symptoms and medication requirements. Questions relating to work environment and employers' actions were included, and each participant completed an assessment of health-related quality of life using the EuroQol Research Foundation EQ-5D. Results: There were 207 completed questionnaires; response rates were 6% primary care, 45% secondary care and 71% Asthma UK. This represented a 13% overall response rate. Self-reported prevalence of WAA was 33% (95% CI 24.4–41.6%). In all, 19% of workers had changed their job because of breathing problems. Workers with WAA reported higher levels of work-related stress. Quality of life using the EQ-5D utility index was lower in those with WAA. Conclusion: WAA is a common problem in asthmatics in GB. This result is in keeping with international prevalence rates. Further research could assist the understanding of the most significant aggravants to asthma at work and help define appropriate interventions by workplaces.